2016
DOI: 10.3389/fnhum.2016.00460
|View full text |Cite
|
Sign up to set email alerts
|

Structural Imaging Changes and Behavioral Correlates in Patients with Crohn’s Disease in Remission

Abstract: Background: Crohn’s disease (CD) is a subtype of inflammatory bowel disease caused by immune-mediated inflammation in the gastrointestinal tract. The extent of morphologic brain alterations and their associated cognitive and affective impairments remain poorly characterized.Aims: We used magnetic resonance imaging to identify structural brain differences between patients with Crohn’s disease in remission compared to age-matched healthy controls and evaluated for structural-behavioral correlates.Methods: Ninete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 75 publications
4
43
1
Order By: Relevance
“…Our study suggests that brain white matter microstructural properties are significantly altered in CD patients. Our findings support the growing number of studies that have applied neuroimaging to examine the neural substrates impacted by the disease as well as its relationship to cognitive or affective processes 5 and disease duration 3,8,20 .…”
Section: Discussionsupporting
confidence: 81%
“…Our study suggests that brain white matter microstructural properties are significantly altered in CD patients. Our findings support the growing number of studies that have applied neuroimaging to examine the neural substrates impacted by the disease as well as its relationship to cognitive or affective processes 5 and disease duration 3,8,20 .…”
Section: Discussionsupporting
confidence: 81%
“…ICA results show CD females had decreased FC of the visual network with the right temporal occipital fusiform gyrus, which supports the multiple ROI findings of altered visual network FC for CD females. Although perhaps not intuitive that visual network changes would be involved in CD, differences in visual processing regions have been reported in previous CD studies, including cortical thickness differences in left lateral occipital cortex (24), hypergyrification of left lingual gyrus (41) for CD, and increased FC within visual medial and frontoparietal networks in IBD (42), and similar reports are seen for other chronic conditions, such as knee osteoarthritis (43), persistent somatoform pain disorder (44), postherpetic neuralgia (45), migraine (46), and fibromyalgia (47). Having recognized the plethora of studies reporting visual system FC alterations in chronic pain populations, Shen et al (48) investigated the FC of visual network nodes in a chronic low back pain population using an ROI analysis and a support vector machine classifier.…”
Section: Networkmentioning
confidence: 84%
“…Investigations into altered brain structure and function in CD have increased; however, the existing body of literature is limited and there is a lack of consistency among the techniques used and the results reported that prohibits any key brain alterations to be identified. Studies of brain structure in CD may be in agreement on one result, altered gray matter (GM) of the superior frontal gyrus, although laterality and direction of alteration are inconsistent (22)(23)(24). Studies of brain function in CD have reported numerous FC alterations with very little overlap (25)(26)(27)(28)(29)(30)(31)(32) aside from some agreement on changes in brain networks or regions involved in executive function and/or default mode (26,30,32).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported significant changes in brain morphometric measures in CD patients compared to age and gender‐matched controls . Additionally, disrupted resting state functional connectivity has been reported in CD patients in remission .…”
Section: Introductionmentioning
confidence: 88%
“…10 We have previously reported significant changes in brain morphometric measures in CD patients compared to age and gender-matched controls. 11 Additionally, disrupted resting state functional connectivity has been reported in CD patients in remission. 12 Thomann et al 12 also reported significant association between disrupted connectivity and anxiety scores in these patients.…”
Section: Introductionmentioning
confidence: 99%